Internal control and its incidence in the management of works in District Municipalities of Pachitea - Huánuco - Albornoz-Romero, Deysi Y. (2019)
The objective of the research was to determine if internal control affects the management of works of the District Municipalities of Pachitea, province and department of Huánuco, during 2017. The study was quantitative, descriptive, prospective and transversal, with a design correlational The sample was made up of 48 construction workers from 4 District Municipalities of the Province of Pachitea, selected through non-probabilistic sampling. The data was collected through two questionnaires: measurement of internal control and the management of municipal works, previously validated, and reliable. The ethical research considerations were applied. Descriptive analysis was performed and the hypothesis was tested by the Sperman Rho test for a p <0.05. According to the results, 39.6% (19) of the sample had perceived that the internal control was adequate, 35.4% (17) of a regular level and 25.0% (12) inadequate. On the other hand, 37.5% (18) reported that there is inefficient management, 33.3% (16) regular management and only 29.2% (14) reported efficient management. It is concluded that there is a positive, moderate and significant correlation between the analyzed variables (rs = 0.476 and p <0.05); therefore, it is affirmed that internal control has a positive impact on the management of works in the District Municipalities of Pachitea.